Basic concepts of psychotherapeutic correction in patients with schizophrenia - Z. Sh. Ashurov; Z. V. Shin; D. P. Kim (Лечащий Врач)
As part of the work carried out, 84 patients undergoing inpatient treatment at the City Clinical Psychiatric Hospital of Tashkent during 2017-2020 were examined. The average age of the subjects was 35 years old, the minimum age was 21 years old, and the maximum age was 57 years old. The average duration of the disease is 6-7 years, the minimum is 1.5 years, and the maximum is 26 years. Patients with a continuous (F 20.x0), paroxysmal progressive course (F 20.x1) and paroxysmal with a stable defect (F 20.x2), with leading paranoid, asthenic and astheno-depressive syndromes, apatoabulic and mixed type of developing defect were studied. A special program of psychotherapeutic correction of patients with schizophrenia has been developed and carried out. Specificity of this program: minimum of negative emotions evoked in patients; emphasis on the positive sides of the personality; interaction is built in an atmosphere of mutual acceptance, conducive to self-expression (physical and spiritual); openness, clear modulation of your emotions and reflection; active position of the leaders.